Организация и перспективы развития экстренной психологической помощи в структуре МЧС - Furmanov, Игорь; Rafal'skaya, Елена (Vestnik of the Institute for Command Engineers of the MES of the Republic of Belarus, 2011)
In article features of the organisation of the emergency psychological help in structure of the Ministry of Emergencies for the citizens injured with act of terrorism in Minsk and workers of the Ministry of Emergencies, taking part in rescue operation on liquidation of consequences of tragedy are considered. Some supervision at rendering of the emergency psychological help to firemen-rescuers are fixed. The expediency is proved and the model of new organizational-regular structure «the Center of the emergency psychological help and support» the Byelorussian Ministry of Emergencies which structure will include existing system of the psychological help of the Byelorussian Ministry of Emergencies is offered.